Professional Socialization of Pre-service Physical Education Teachers in Hong Kong Institute of Education: 香港敎育學院體育師訓生職化過程的探索 - LI, Chung (Asian Journal of Physical Education & Recreation, 2000)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This paper presents a qualitative study with the use of the interpretive paradigm to capture subjective meanings that pre-service Physical Education (PE) teachers gave to their professional socialization process at the early stage of their two-year full-time teacher-training program. Data concerning their actions, feelings and reflection on their practical, pedagogical and theoretical modules were collected through interviewing and writing of reflective journal. Participants were analyzed according to their types namely, "athletes", "idealists", "pragmatists", "followers" and "the insecure group" while joining the program. It was interesting to find that they all articulated their professional learning to the "process knowledge" through experience rather than "propositional" one in the form of discipline based and theoretical conceptions regardless of their types. The findings provide information about how pre-service PE teachers learn and develop their professional knowledge, which in return, generate implications on how the Physical Education Teacher Education (PETE) program can be implemented effectively in Hong Kong. 本文章以詮釋理念來探索香港敎育學院體育學系本科生職化的過程，研究對象為二十位來自體育學系的本科生，對部份師資培訓課程及經歷作出回顧及分析，藉此了解其學習模式及職化過程，並對現有的課程作出了探討及建議。